Quedan los huesos - Ward, Jesmyn; Ward, Jesmyn; Montolió, Célia (Madrid : Siruela, 2013)
Enduring a hardscrabble existence as the children of alcoholic and absent parents, four siblings from a coastal Mississippi town prepare their meager stores for the arrival of Hurricane Katrina while struggling with such challenges as a teen pregnancy and a dying litter of prize pups.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: African American children -- Fiction; African American teenage girls -- Fiction; Brothers and sisters -- Fiction; Motherless families -- Fiction; African American families -- Mississippi -- Fiction; Rural poor -- Mississippi -- Fiction; Hurricane Katrina, 2005 -- Fiction; Gulf Coast (Miss.) -- Fiction; Domestic fiction; Electronic books